Marketing of milkfish in Iloilo City. - De La Gente, Alice Joan S.
This study describes the marketing practices, costs, net farm price received by the producers, gross margin received by the middlemen and the problems encountered in milkfish marketing in Iloilo City. Primary data was gathered from 24 producers who were interviewed about their last harvest and 56 middlemen who were interviewed about their last week's transaction., Of the total volume sold by the producers (30360 kg.), 86.83 went to the commission men. The highest price, P55/kg. was received by the producers from the institutional buyer the lowest price, P38.48/kg. was received from the commission men. (p)The marketing costs received were P5.40/kg. and P5.61/kg. by the producers who sold locally and in Manila, respectively. The commission men's fee accounted for the largest share of marketing costs of both the producers who sold locally (P2.36/kg) and in Manila (P2.50/kg). The net farm prices received were P35.30/kg and P33.72/kg by producers who sold milkfish locally and in Manila, respectively. The producers whose milkfish were sold in Manila received a lower average price with higher marketing costs. By market function, seven types of middlemen were identified: commission man, buyer-seller, wholesaler, wholesaler-shipper, buyer-seller-retailer, wholesaler-retailer and retailer. The middlemen sold a total volume of 57070.5 kg inside (64.03) and outside (35.97) the survey area. The commission men sold the highest volume (34.71) of milkfish. The wholesaler-retailers received the highest average selling price of P47.75/kg. The wholesaler-shippers had the highest gross margin (P8.22/kg) while the wholesaler-retailers who sold outside the survey area had the highest net return (P3.97/kg). The low price of milkfish was the main problem of both producers and middlemen. The milkfish marketing involved many channels primarily brought about by the presence of too many types of middlemen who practiced intertrading among each other. Thus, there was a duplication of the performance of marketing practices among types of middlemen which increased the marketing costs and correspondingly raised the prices of milkfish.